Study on the selection process of junior weightlifters in Romania - Calin, G.; Ciorba, C.; Gheorghiu, G. (Science, Movement & Health, 2022)
Our study aims to provide a clearer picture of how weightlifting coaches in Romania make the selection of future performers. In performance sports, the selection process is extremely important, and weightlifting is no exception to this rule. In the 21st century, in order to hope for the best possible results, this process should be based on studies and research of the relevant literature. Methods. In view of the proposed objective, a questionnaire was created for weightlifting coaches in Romania. The questionnaire consists of two parts, the first requesting demographic data (4 items) and the second requesting the expert opinion on the selection process (15 items). For each item in the second part, the coaches had to choose from 5 options of answer designed based on the Likert scale. Results & Discussions. Out of the total number of active weightlifting coaches in Romania in 2021, 56,3% agreed to complete the questionnaire (N = 33). Given the criteria on the basis on which these coaches make the selection, we can say that many of them are not in conformity with specialized studies. For example, many of the coaches said that the technical and tactical factor represent important criteria in the selection process. Conclusion. In Romania, for the weightlifting branch, there is a need for a professional selection system, based on the latest research in the field, in order to help coaches.